The Big Three Health Behaviors and Mental Health and Well-Being Among Young Adults: A Cross-Sectional Investigation of Sleep, Exercise, and Diet - Wickham, Shay-Ruby; Amarasekara, Natasha A.; Bartonicek, Adam; Conner, Tamlin S. (Frontiers in Psychology, 2020)
Background: Sleep, physical activity, and diet have been associated with mental health and well-being individually in young-adults. However, which of these “big three” health behaviors most strongly predicts mental health and well-being, and their higher-order relationships in predictive models, is less known. This study investigated the differential and higher-order associations between sleep, physical activity, and dietary factors as predictors of mental health and well-being in young-adults. Method: In a cross-sectional survey design, 1,111 young-adults ages 18-25 from New Zealand and the United States answered an online survey measuring typical sleep quantity and quality, physical activity, and consumption of raw and processed fruit and vegetables, fast food, sweets, and soda, along with extensive covariates (including demographics, socioeconomic status, body mass index, alcohol use, smoking, and health conditions) and the outcome measures of depressive symptoms (measured by the CES-D) and well-being (measured by the Flourishing Scale). Results: Controlling for covariates, sleep quality was the strongest predictor of depressive symptoms and well-being, followed by sleep quantity and physical activity. Only one dietary factor— raw fruit and vegetable consumption—predicted greater well-being but not depressive symptoms when controlling for covariates. There were some higher order interactions among health behaviors in predicting the outcomes, but these did not survive cross-validation. Conclusion: Sleep quality is an important predictor of mental health and well-being in young-adults, whereas physical activity and diet are secondary but still significant factors. Although strictly correlational, these patterns suggest that health interventions maximizing mental health and well-being within young-adults could prioritize sleep quality.